Pengaruh Pemberian Sustained Natural Apophyseal Glides untuk Meningkatkan Kemampuan Fungsional pada Pasien Nyeri Leher Non Spesifik - Bagas Prayoga; Suhardi Suhardi; Afif Ghufroni (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Non-specific neck pain is a common musculoskeletal complaint among industrial workers, often caused by prolonged static working postures and inadequate application of ergonomic principles. This condition can lead to muscle spasms, decreased joint mobility, and reduced functional ability of the neck. One physiotherapy intervention that can be used to address this condition is the Sustained Natural Apophyseal Glides (SNAGs) technique. Objectives: To determine the effect of Sustained Natural Apophyseal Glides on improving functional ability in patients with non-specific neck pain. Methods: This study used an experimental research design with a one-group with control design involving 30 research subjects who were randomly divided into groups. Functional ability was measured using the Neck Disability Index (NDI) questionnaire. Data analysis was performed using the Wilcoxon test and the Mann–Whitney test. Results: The results showed that the application of SNAGs had a significant effect on improving functional ability in patients with non-specific neck pain (p = 0.001; p < 0.05), whereas the control group showed no significant change with a p-value of 0.059 (p > 0.05). Conclusion: SNAGs are effective in improving functional ability in patients with non-specific neck pain. Keywords: Non-Specific Neck Pain, SNAGs, Functional Abilities, Neck Disability Index.